Evaluasi Pelaksanaan Praktik Pembentukan Bahan Bengkel Fabrikasi Jurusan Pendidikan Teknik Mesin Fakultas Teknik Universitas Negeri Yogyakarta - Arif Marwanto; Aan Ardian; Suyanto Suyanto (Jurnal Dinamika Vokasional Teknik Mesin, 2017)
The implementation of practice-work learning need to be evaluated periodically to determine wether the equipments and the learning methods are appropriate to the main purpose of learning, which is the establishment of learners' competency. The evaluation process in this research was carried out by adopting the CIPP evaluation methods. The research objects are lecturers and students participating in the Material Forming Practice course. Data were collected using documentation, observation and questionnaires and were analyzed using descriptive analysis. The results show that the implementation of Material Forming Practice course in the half semester of academic year 2016/2017 was very successful. Barriers faced by the lecturers were the lack of students' comprehension in flat pattern drawing, mathematical analysis skills, lack of motivation in reading jobsheet, and the lack of students' adaptation to the practice environment. Barriers faced by the students came from the lecturers, workpiece materials, low category workshop conditions, the shop equipments are in moderate category, whereas jobsheets and technicians are in the very low category. The condition of the equipments in terms of quantity is sufficient, but in terms of quality, many still needs repairs and renewals. The students' learning achiements in the midterm semester was the ability to finish 4 jobs with marks as follow: 53% were graded "A", 35% were graded "B"and the remaining 12% were graded "C". Penelitian ini bertujuan untuk mengetahui kesesuaian peralatan dan pelaksanaan pembelajaran dengan tujuan akhir pembelajaran yaitu pembentukan kompetensi mahasiswa. Metode yang digunakan mengadopsi metode evaluasi CIPP. Objek penelitian adalah dosen pengampu dan mahasiswa peserta mata kuliah praktik Pembentukan Bahan tahun ajaran 2016/2017. Metode pengumpulan data menggunakan dokumentasi, observasi, dan angket. Data dianalisis dengan teknik analisis deskriptif. Hasil penelitian menunjukkan bahwa pelaksanaan praktik Pembentukan Bahan selama setengah semester terlaksana dengan sangat baik. Hambatan yang dialami dosen yaitu kurangnya kemampuan mahasiswa dalam memahami gambar bentangan, analisis matematika, adaptasi dengan lingkungan praktik, dan malas membaca jobsheet. Hambatan mahasiswa dari dosen, bahan, dan kondisi bengkel termasuk kategori rendah, alat termasuk kategori sedang, jobsheet dan teknisi termasuk kategori rendah sekali. Kondisi peralatan secara kuantitas mencukupi, tetapi kualitasnya perlu perbaikan dan peremajaan. Pada pertengahan semester mahasiswa mampu menyelesaikan 4 materi pekerjaan dengan perolehan nilai A sebanyak 53%, nilai B sebanyak 35% dan nilai C sebanyak 12%.